Application of Law Enforcement Due Process System in Law Against Child Crimes - Yoslan K. Koni; Marten Bunga; Dince Aisa Kodai; Nurwita Ismail; Mega S Tangahu (Faculty of Law, Musamus University, 2021)
Purpose To know and analyze the application of the due process of law system in law enforcement against child crime, to find out and analyze what are the factors that influence law enforcement on the implementation of the due process of law system. By using this type of research is Normative research. Normactive research is meant as legal research which studies normative law. The normative approach method is used to examine the aspects of the law according to laws and regulations relating to the implementation of the Due Process Of Law system in Criminal law, especially against child crimes. The results of the research show that law was born to humanize humans, so law enforcement or law enforcement must provide benefits or benefits to society. The quality of development and law enforcement is demanded by society at this time not only for formal quality, but also for material / substantial quality. Substantively. the implementation of child protection must be in accordance with relevant professional ethics, to prevent deviant behavior in the exercise of authority, power and strength in the implementation of child protection. The concept of due process is like prioritizing the rule of law, law enforcement officers must recognize, respect, protect and guarantee the rights of suspects. Law and justice is an integrity between normative idealism and human action. If the three of them are no longer combined and become judicial cohesion, then what will generally occur is a lameness whose mode and packaging is destructive and dysmunctional, which then makes it easy for someone and the public to draw conclusions or create estimates, there has been a play and a dramatization project that is still under the guise of carrying out their duties. , what is meant in it is to impose a legal decision.